The Persistence of Tinnitus after Acoustic Neuroma Surgery. (August 2016) - Bell, Jason R.; Anderson-Kim, Sara J.; Low, Christopher; Leonetti, John P.
Objective: Examine possible prognostic factors for the persistence of tinnitus after acoustic neuroma resection. Study Design: Case series with chart review. Setting: Tertiary academic medical center. Subjects and Methods: The records of 166 patients who underwent acoustic neuroma resection from 2009 to 2014 were reviewed. Patients were asked to complete a survey, including the Tinnitus Handicap Inventory, 1 to 6 years postoperatively. Results: Of the 53 patients who completed the survey, 17% reported that their tinnitus resolved; 9% reported improvement; 23% reported no change; 43% reported that their tinnitus worsened; and 8% were unsure. Respondents ≥50 years old and those with nonserviceable hearing preoperatively were more likely to report that their tinnitus resolved or improved ( P < .01 and P = .02, respectively). Respondents <50 years old and those with serviceable hearing preoperatively were more likely to report that their tinnitus was the same or worse ( P < .001 and P = .036, respectively). Respondents with age <50 years, serviceable hearing preoperatively, and residual tumor had a higher average Tinnitus Handicap Inventory score ( P = .016, P = .048, and P = .047, respectively). Sex, tumor size, surgical approach, hearing preservation, and cochlear nerve status did not correlate with the prognosis of tinnitus postoperatively. Respondents whose tinnitus resolved postoperatively were more likely to report being "very satisfied" with their care ( P = .012). Conclusion: In this study, 83% of respondents had persistent tinnitus after acoustic neuroma resection. The prognosis of tinnitus was worse for younger respondents, those with serviceable hearing preoperatively, and those with residual tumor postoperatively. Respondents' satisfaction was higher if their tinnitus resolved.